2021
DOI: 10.29252/wjps.10.1.96
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Clinical and Histopathological Effects of Topical Psyllium (Plantago ovata) Powder and Silver Sul-fadiazine on Second-Degree Burn Wound Healing in Rats

Abstract: BACKGROUND Burn wounds are a worldwide health problem, leading to physical and psychological disabilities in all age’s groups. With regard to absorbent properties of Plantago ovata mucilage which can decrease wound moisture, we aimed to compare the effect of silver sulfadiazine (SSD) 1% and powdered P. ovata on second-degree burn wound healing in rats. METHODS This experimental study was conducted on 30 male Wistar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…In the histological analysis with Masson’s Trichrome staining (MT), it was observed that in all treated groups a marked presence of collagen was identified, but only the group treated PVA+A+L 14 days was significantly different from the control (Table 4; Figure 8), showing that this treatment was more efficient in this experimental design, similar to the findings of 39 in histopathological studies of scar tissue from 2nd degree burns treated with Plantago ovata and silver sulfadiazine. In this line, many studies seeking treatment for skin lesions caused by burns use herbal medicines such as Aloe vera and suggest that this herbal medicine stimulates fibroblasts and, in turn, collagen in the granulation tissue.…”
Section: Resultssupporting
confidence: 75%
“…In the histological analysis with Masson’s Trichrome staining (MT), it was observed that in all treated groups a marked presence of collagen was identified, but only the group treated PVA+A+L 14 days was significantly different from the control (Table 4; Figure 8), showing that this treatment was more efficient in this experimental design, similar to the findings of 39 in histopathological studies of scar tissue from 2nd degree burns treated with Plantago ovata and silver sulfadiazine. In this line, many studies seeking treatment for skin lesions caused by burns use herbal medicines such as Aloe vera and suggest that this herbal medicine stimulates fibroblasts and, in turn, collagen in the granulation tissue.…”
Section: Resultssupporting
confidence: 75%
“…15,16 While extensive research has been conducted into identifying the efficacy of sea buckthorn in wound healing in non-human samples, [17][18][19] rare research programs examining the effect of sea buckthorn in burns of human samples have been carried out. 20 Thus, considering SSD is the most common and the main medicine used in routine treatment of burn wounds in our country Iran, 21 researchers of the present study designed this controlled clinical trial aiming at evaluating the period of wound healing with sea buckthorn topical cream dressings for the second-degree burns and comparing the results with the 1% SSD dressings.…”
mentioning
confidence: 99%